2017
DOI: 10.1002/stem.2660
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Expressed in Hepatocellular Carcinoma, TEC, Controls Pluripotency and Early Cell Fate Decisions of Human Pluripotent Stem Cells via Regulation of Fibroblast Growth Factor-2 Secretion

Abstract: Human pluripotent stem cells (hPSC) require signaling provided by fibroblast growth factor (FGF) receptors. This can be initiated by the recombinant FGF2 ligand supplied exogenously, but hPSC further support their niche by secretion of endogenous FGF2. In this study, we describe a role of tyrosine kinase expressed in hepatocellular carcinoma (TEC) kinase in this process. We show that TEC-mediated FGF2 secretion is essential for hPSC self-renewal, and its lack mediates specific differentiation. Following both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Human embryonic stem cells (hESC) or induced pluripotent stem cells (hiPSC) express FGFR1-4 (Supplementary Material, Table S1) (16), exhibit a particularly strong response to FGF stimulus and require continuous stimulation with high FGF2 doses for self-renewal and maintenance of stemness (17). Treatment with FGF2 significantly (P < 0.001) shortened primary cilia in hESC and hiPSC when compared with untreated cells, while chemical inhibition of high endogenous levels of FGF signaling in hESC and hiPSC (18) extended primary cilia length over the controls (Fig. 2B).…”
Section: Sustained Activation Of Fgf Signaling Results In Shortening Of Primary Ciliamentioning
confidence: 99%
“…Human embryonic stem cells (hESC) or induced pluripotent stem cells (hiPSC) express FGFR1-4 (Supplementary Material, Table S1) (16), exhibit a particularly strong response to FGF stimulus and require continuous stimulation with high FGF2 doses for self-renewal and maintenance of stemness (17). Treatment with FGF2 significantly (P < 0.001) shortened primary cilia in hESC and hiPSC when compared with untreated cells, while chemical inhibition of high endogenous levels of FGF signaling in hESC and hiPSC (18) extended primary cilia length over the controls (Fig. 2B).…”
Section: Sustained Activation Of Fgf Signaling Results In Shortening Of Primary Ciliamentioning
confidence: 99%
“…This was supported by an investigation carried out by Chen et al [ 127 ] exploring TEC protein expression in hepatocellular carcinoma and TEC phosphorylation in 200 specimens of cancerous and non-cancerous liver tissue. A more recent study by Vanova et al [ 128 ] with interest in the expression of TEC in hepatocellcular carcinoma, identified TEC as a regulator in controlling pluripotent cell fate in human pluripotent stem cells, acting through the regulation of fibroblast growth factor-2 secretion. Such studies provide further support and evidence of the broad activities and roles of tyrosine kinase preferentially expressed in hepatocellular carcinoma.…”
Section: Non Receptor Tyrosine Kinase Familiesmentioning
confidence: 99%
“…For example, mutations in TEC (Tec protein tyrosine kinase, c.A122G, p.Y41C) and ABR (Active breakpoint cluster region-related protein, c.C1079G, p.P360R) were embedded in PH (Pleckstrin homology) domain, a critical domain to bind phosphoinositides for regulation of intracellular signaling [ 44 ]. Tec kinase is an integral component of T cell signaling and controls early cell fate decisions of human pluripotent stem cells via regulation of fibroblast growth factor-2 secretion [ 45 ]. ABR is an important regulator of neuronal development [ 46 ].…”
Section: Discussionmentioning
confidence: 99%